2022
DOI: 10.1097/md.0000000000028599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylene blue on hemodynamic and metabolic response in septic shock patients

Abstract: Introduction: Septic shock is a lethal disease responsible for a large proportion of deaths in the Intensive Care Unit (ICU), even with therapy centered on fluid resuscitation, use of vasopressors and empirical antibiotic therapy applied within the first hour of diagnosis. Considering the multifactorial pathophysiology of septic shock and the mechanism of action of vasopressors, some patients may not respond adequately, which can lead to the maintenance of vasodilatation, hypotension and increased morbidity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Figure 1 summarizes the study population and study design. Eighty patients were enrolled upon signing the informed consent form by their next of kin and were randomly allocated into two groups according to the previously published protocol [13]. After withdrawing based on clinical status (n = 48), a total of 42 patients were included in the present study; 23 patients were allocated to the control group, and 19 were randomized to the MB group.…”
Section: Study Design Population and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 summarizes the study population and study design. Eighty patients were enrolled upon signing the informed consent form by their next of kin and were randomly allocated into two groups according to the previously published protocol [13]. After withdrawing based on clinical status (n = 48), a total of 42 patients were included in the present study; 23 patients were allocated to the control group, and 19 were randomized to the MB group.…”
Section: Study Design Population and Samplingmentioning
confidence: 99%
“…Several studies have proposed that MB can treat circulatory shock secondary to vasoplegia via nitric oxide (NO) [7,8,[10][11][12][13][14][15]. In a rat model of endotoxemia induced by lipopolysaccharide (LPS) and treated with MB, complete prevention of leukocyte rolling and adhesion to the endothelium was observed, resulting in a consistent systemic blood pressure response and a decreased need for vasoactive medications [16].…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic drugs focus on endothelial vasoreactivity, inflammation, oxidative stress, and coagulation/anticoagulation balance. Table 2 (34)(35)(36)(37)(38)(39)(40) presents the major recent trials focusing on microcirculation during sepsis. Overall, while some studies showed an improvement in microcirculatory parameters, very few interventions succeeded in reducing mortality in critically ill septic patients.…”
Section: Inotropes/vasopressorsmentioning
confidence: 99%
“…This case series aims to report 6 cases of patients treated with standard therapy associated with MB in the first 72 hours of septic shock onset using a protocol predefined in the literature. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%